2011
DOI: 10.4028/www.scientific.net/msf.700.1
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Behavior of Cuprate Superconductors from NMR Shifts

Abstract: NMR spin shift data of La1:85Sr0:15CuO4, HgBa2CuO4+ at ambient pressure, andof YBa2Cu4O8 at pressure up to 63 kbar are discussed that fail the traditional single-electronicuid picture used for the discussion of NMR data. Instead the results point to a commonexplanation for all three systems in terms of two electronic components. One of them hasa temperature-dependent magnetic susceptibility while the second component, as well as itscoupling to the rst component, are constant above the superconducting transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Here, we present a comprehensive set of Cu and Hg NMR shifts and linewidths data for an underdoped (T c =74 K) and an optimally doped (T c =97 K) sample of HgBa 2 CuO 4+δ . In separate accounts 22,23 we found that the spin shifts cannot be explained with a single Tdependent spin component, but with a two-component scenario where the spin susceptibility is written as the sum of two terms, χ (T, x) = χ 1 (T, x) + χ 2 (T, x), where the first term (χ 1 ) carries the pseudogap feature discovered by NMR shifts measurements, i.e., it is Tdependent far above T c . 24 The second susceptibility (χ 2 ) is T independent above T c , but it quickly disappears below T c , similar to what was concluded previously for La 1.85 Sr 0.15 CuO 4 , and that reminds one of Fermi-liquidlike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a comprehensive set of Cu and Hg NMR shifts and linewidths data for an underdoped (T c =74 K) and an optimally doped (T c =97 K) sample of HgBa 2 CuO 4+δ . In separate accounts 22,23 we found that the spin shifts cannot be explained with a single Tdependent spin component, but with a two-component scenario where the spin susceptibility is written as the sum of two terms, χ (T, x) = χ 1 (T, x) + χ 2 (T, x), where the first term (χ 1 ) carries the pseudogap feature discovered by NMR shifts measurements, i.e., it is Tdependent far above T c . 24 The second susceptibility (χ 2 ) is T independent above T c , but it quickly disappears below T c , similar to what was concluded previously for La 1.85 Sr 0.15 CuO 4 , and that reminds one of Fermi-liquidlike behavior.…”
Section: Introductionmentioning
confidence: 99%